Crucial role of nicotinic α5 subunit variants for Ca2+ fluxes in ventral midbrain neurons. Issue 8 (24th April 2015) - Sciaccaluga, Miriam; Monconi, Claudia; Martinello, Katiuscia; Catalano, Myriam; Bermudez, Isabel; Stitzel, Jerry A.; Maskos, Uwe; Fucile, Sergio
Abstract : Neuronal nicotinic acetylcholine receptors (nAChRs) containing the α5 subunit modulate nicotine consumption, and the human CHRNA5 rs16969968 polymorphism, causing the replacement of the aspartic acid residue at position 398 with an asparagine (α5DN), has recently been associated with increased use of tobacco and higher incidence of lung cancer. We show that in ventral midbrain neurons, the α5 subunit is essential for heteromeric nAChR‐induced intracellular‐free Ca 2+ concentration elevations and that in α5‐/‐ mice, a class of large‐amplitude nicotine‐evoked currents is lost. Furthermore, the expression of the α5DN subunit is not able to restore nicotinic responses, indicating a loss of function by this subunit in native neurons. To understand how α5DN impairs heteromeric nAChR functions, we coexpressed α4, α5, or α5DN subunits with a dimeric concatemer (β2α4) in a heterologous system, to obtain nAChRs with fixed stoichiometry. Both α5(β2α4)2 and α5DN(β2α4)2 nAChRs yielded similar levels of functional expression and Ca 2+ permeability, measured as fractional Ca 2+ currents (8.2 ± 0.7% and 8.0 ± 1.9%, respectively), 2‐fold higher than α4 (β2α4)2 . Our results indicate that the loss of function of nicotinic responses observed in α5DN‐expressing ventral midbrain neurons is neither due to an intrinsic inability of this subunit to form functional nAChRs nor to an altered Ca 2+ permeability but likely to intracellular modulation.—Sciaccaluga, M., Moriconi, C., Martinello, K., Catalano, M., Bermudez, I., Stitzel, J. A., Maskos, U., Fucile, S. Crucial role of nicotinic α5 subunit variants for Ca 2+ fluxes in ventral midbrain neurons. FASEB J. 29, 3389‐3398 (2015). www.fasebj.org